2011
DOI: 10.1097/scs.0b013e3182323fbe
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Odontogenic and Nonodontogenic Cysts

Abstract: The jaws are host to a variety of cysts due in large part to the tissues involved in tooth formation. Odontogenic cysts (OCs) are unique in that they affect only the oral and maxillofacial region. There are few studies from sub-Saharan Africa. This study was aimed at describing the pattern of various types of cysts in the oral and maxillofacial region in a Kenyan population. This was done at the Departments of Oral and Maxillofacial Surgery and Oral Medicine and Pathology, University of Nairobi Dental Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
8
14
2
Order By: Relevance
“…In this study while ameloblastoma comprised majority (65.6%) of the odontogenic tumors it was slightly below the findings by Simon et al (2005) in which ameloblastoma constituted 80.1% of all odontogenic tumors [11]. Ameloblastoma has also been reported to be the most common odontogenic tumor in several other studies from other countries [2][3][4]8].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In this study while ameloblastoma comprised majority (65.6%) of the odontogenic tumors it was slightly below the findings by Simon et al (2005) in which ameloblastoma constituted 80.1% of all odontogenic tumors [11]. Ameloblastoma has also been reported to be the most common odontogenic tumor in several other studies from other countries [2][3][4]8].…”
Section: Discussioncontrasting
confidence: 72%
“…The occurrence of the odontogenic tumors and tumor-like lesions vary from one country to the other. In Tanzania, they were reported to comprise about 12% of all tumors of the orofacial region [2] and elsewhere in Africa, they accounted for 10% to 14% of all orofacial tumors [3,4]. Their prevalence was less than 5% in Brazil, China and Pakistan [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported higher prevalence than our: 59% in Turkey (22); 72.5% and 61.4% in Brazil (9,10). The values reported in series using 2005 WHO classification ranged from 38.7% in Kenyans (16) to 64.3% in Saudis (17). A putative explanation to justify this high prevalence of radicular cyst could be related to caries.…”
Section: Discussionmentioning
confidence: 99%
“…The duct is known to regress in fetal life, however the persistence of ductal epithelium leads to cyst formation. As it is considered to be the most common non-odontogenic cyst of the gnathic bones [2]. The mean medio-lateral diameter of the incisive foramen ranged from 1.40 mm to 5.90 mm [3], cysts larger than the normal anatomical feature can only be distinguished from incisive foramen.…”
Section: Introductionmentioning
confidence: 99%